UJI AKTIVITAS ANTIBAKTERI DAN ANALISIS BIOAUTOGRAFI KROMATOGRAFI LAPIS TIPIS EKSTRAK ETANOL DAUN SRIKAYA (ANNONA SQUAMOSA L) TERHADAP ENTEROCOCCUS FAECALIS SECARA IN VITRO - Isti Daristivia Jangnga; Portuna Putra Kambaya; Khemasili Kosala (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: Endodontic treatment is a treatment to maintain teeth that have undergone pulp or periapical infections to stay as long as possible in the oral cavity and restore them to their original form and function in the mastication system. The main causes are bacteria Enterococcus faecalis. The purpose of this study is to investigate the effect of extract srikaya leaves on the growth of Enterococcus faecalis bacteria in vitro and to analyze secondary metabolites that have antibacterial activity.Method: Experimental study used Kirby Bauer diffusion test. The researchdesign was post test only control group design and Bioautography TLC design. There was 5 treatment groups : concentration 25%, 50%, 75% extract of ethanol of srikaya leaves, positive control group (chlorhexidine gluconate 0,2%), and negative control group ( DMSO 10%). Statistical analysis used One Way Anova and Post Hoc Test Tukey.Results: Extract of Srikaya Leaves can inhibit the growth of Enterococcus faecalis bacteria in concentrations of 25%, 50%, and 75% and detectablesecondary metabolites show inhibit zone.Conclusion: The extract of ethanol leaves of srikaya (Annona squamosa L) have the effect of inhibiting the growth of Enterococcus faecalis bacteria and secondary metabolites have effect in inhibiting bacterial growth.